"There"s no-one you can trust to talk to here": Churches and internally displaced survivors of sexual violence in Medellín, Colombia - Roux, Elisabet Le (HTS teologiese studies, 2019)
After over 50 years of warfare, Colombia has the largest internally displaced population in the world. Internally displaced women appear to be particularly at risk of sexual violence. Religious belief and affiliation can potentially impact the coping of internally displaced and sexual violence survivors in a country where 79% of the population self-identifies as Catholic and 13% as Protestant. This article explores the complex intersect of religion, internal displacement and sexual violence by drawing on interview and focus group data collected from sexual violence survivors and faith leaders in a community of internally displaced survivors in Medellín, Colombia. The qualitative empirical data are used to unpack displaced survivors’ experiences and needs, and reflect on churches’ response to internally displaced and sexual violence survivors more broadly. We see that by offering a spiritual response to a traumatic event and its consequences, as well as a sense of community and belonging, churches can contribute to the coping ability and healing process of displaced survivors. A theological approach to sexual violence can ensure that sexual violence prevention and response is seen as part of churches’ core mandate and mainstreamed in their activities, and by leveraging their ability to influence community and individual beliefs and behaviours, churches can counter the inter-generational cycle of intra-familial violence that so often emerges in the settings of internally displaced persons.